2002
DOI: 10.1096/fj.02-0149fje
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylcholine synthesis is elevated in neuronal models of Gaucher disease due to direct activation of CTP:phosphocholine cytidylyltransferase by glucosylceramide

Abstract: Glucosylceramide (GlcCer) accumulates in the inherited metabolic disorder, Gaucher disease, because of the defective activity of lysosomal glucocerebrosidase. We previously demonstrated that upon GlcCer accumulation, cultured hippocampal neurons exhibit modified growth patterns, altered endoplasmic reticulum density, and altered calcium release from intracellular stores. We here examined the relationship between GlcCer accumulation and phospholipid synthesis. After treatment of neurons with an active site-dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 74 publications
3
54
0
Order By: Relevance
“…5 However, lyso-GSLs accumulate at much higher levels in GSL storage diseases, such as Gaucher and Krabbe's disease, particularly in the brain, and the lyso-GSLs, rather than the GSLs, have been implicated in the mechanisms underlying disease pathology, especially neuropathology (34,64). Irrespective of the physiological relevance of lyso-GSLs in mobilizing Ca 2ϩ from microsomes, the specificity of GlcCer compared with both other GSLs and lyso-GSLs on Ca 2ϩ mobilization reported both in this study in microsomes and in our previous study in cultured neurons (22), and our recent study on activation of CTP:phosphocholine cytidylyltransferase by GlcCer (60), suggest that GlcCer is an important intracellular messenger that plays keys roles in both the regulation of phospholipid synthesis and in intracellular Ca 2ϩ homeostasis.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…5 However, lyso-GSLs accumulate at much higher levels in GSL storage diseases, such as Gaucher and Krabbe's disease, particularly in the brain, and the lyso-GSLs, rather than the GSLs, have been implicated in the mechanisms underlying disease pathology, especially neuropathology (34,64). Irrespective of the physiological relevance of lyso-GSLs in mobilizing Ca 2ϩ from microsomes, the specificity of GlcCer compared with both other GSLs and lyso-GSLs on Ca 2ϩ mobilization reported both in this study in microsomes and in our previous study in cultured neurons (22), and our recent study on activation of CTP:phosphocholine cytidylyltransferase by GlcCer (60), suggest that GlcCer is an important intracellular messenger that plays keys roles in both the regulation of phospholipid synthesis and in intracellular Ca 2ϩ homeostasis.…”
Section: Discussionsupporting
confidence: 43%
“…However, our understanding of the intracellular distribution of GSLs may need to be re-evaluated in light of recent findings demonstrating that GlcCer affects a number of activities associated with the ER and other intracellular organelles (59,60). Indeed, a recent study demonstrated that sphingolipid-specific glycosyltransferases are found in a mitochondrialassociated ER subcompartment of rat liver (61) which could not be ascribed to contaminating Golgi apparatus membranes.…”
Section: Discussionmentioning
confidence: 99%
“…The neuronal degeneration has been shown to be associated with increased levels of GlcCer in the neuronal endoplasmic reticulum and with abnormally enhanced agonist-induced calcium release from GD type II brain microsomes, which served to make the neurons more sensitive to glutamate-induced neurotoxicity. Similarly, in the neuronal models of GD, it was shown that GlcCer directly activated phospholipid synthesis by activation of CTP:phosphocholine cytidylyltransferase (CCT), which was shifted from cytosol to the endoplasmic reticulum (Bodennec et al 2002;Korkotian et al 1999;Pelled et al 2005). All these phenomena could be explained by the transfer of the uncleaved lysosomal GlcCer into the neuronal endoplasmic reticulum (Bodennec et al 2002;Jmoudiak and Futerman 2005).…”
Section: Glucosylceramide Transfermentioning
confidence: 94%
“…Similarly, in the neuronal models of GD, it was shown that GlcCer directly activated phospholipid synthesis by activation of CTP:phosphocholine cytidylyltransferase (CCT), which was shifted from cytosol to the endoplasmic reticulum (Bodennec et al 2002;Korkotian et al 1999;Pelled et al 2005). All these phenomena could be explained by the transfer of the uncleaved lysosomal GlcCer into the neuronal endoplasmic reticulum (Bodennec et al 2002;Jmoudiak and Futerman 2005). The role of GlcSph in neuronal degeneration is mentioned below.…”
Section: Glucosylceramide Transfermentioning
confidence: 95%
“…Individual embryos were genotyped (30). Cortices were removed from individual embryos on embryonic day 17 and lipids extracted as described below.…”
Section: Animalsmentioning
confidence: 99%